Asymptomatic patent processus vaginalis is a risk for developing external inguinal hernia in adults: A prospective cohort study. (April 2021) - Watanabe, Takashi; Yokoyama, Shozo; Iwahashi, Makoto; Mori, Kazunari; Yamade, Naohisa; Yamaguchi, Kazuya; Takifuji, Katsunari; Mitani, Yasuyuki; Matsuda, Kenji; Yamaue, Hiroki
Abstract: Background: Inguinal hernia repair is common for children and adults across the world, but the mechanism behind hernia onset still requires elucidation. This prospective study aims to determine whether patent processus vaginalis (PPV) is a factor in the development of external inguinal hernias. Method: We enrolled 1008 patients who underwent laparoscopic surgery and in whom the inguinal region was observed. If processus vaginalis existed, we measured the diameter and length. Patients were followed for three years after surgery to investigate the incidence of external inguinal hernias. Result: No significant differences were found between age groups. Furthermore, no difference could be recognized in length or opening diameter of the PPVs between age groups. Three-year follow up was possible for 765 of 1008 patients enrolled in this study (76%), eight of whom, all male, developed external inguinal hernia during this period. Multivariate analysis for onset of inguinal hernia onset in male patients showed that PPV and length of the right PPV were independent risk factors for development of external inguinal hernia. Conclusion: The patency rate, length, and diameter of the processus vaginalis do not differ according to age. The patency of the processus vaginalis in male patients is an independent risk factor for development of external inguinal hernia in adults. Highlights: The patency rate, length, and diameter of the processus vaginalis do not differ according to age. That the patency of the processus vaginalis in male is an independent risk factor for development of external inguinal hernia in adults. Length of the right peritoneal sheath may be a factor in the development of inguinal hernias in males.